2022
DOI: 10.3390/cells11162498
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Alteration of BMDM In Vitro Using Small Interfering RNA

Abstract: Autologous macrophage transfer is an emerging platform for cell therapy. It is anticipated that conventional macrophage reprogramming based on ex vivo polarization using cytokines and ligands of TLRs may enhance the therapeutic effect. We describe an alternative approach based on small interfering RNA (siRNA) knockdown of selected molecular cues of macrophage polarization, namely EGR2, IRF3, IRF5, and TLR4 in Raw264.7 monocyte/macrophage cell line and mouse-bone-marrow-derived macrophages (BMDMs). The impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…To further investigate the role of IL‐28A in the regulation of M1 macrophages, mouse bone marrow cells were cultured with complete DMEM with GM‐CSF for 7 days. On day 7, the BMDMs were replated, and untreated (M0, CD11b + F4/80 + ) macrophages from WT and IL‐28A −/− mice were stimulated with LPS and IFN‐γ 43,44 . Cells were collected to detect the proportion of F4/80 + CD86 + cells after 24 h, which are indicative of M1 macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the role of IL‐28A in the regulation of M1 macrophages, mouse bone marrow cells were cultured with complete DMEM with GM‐CSF for 7 days. On day 7, the BMDMs were replated, and untreated (M0, CD11b + F4/80 + ) macrophages from WT and IL‐28A −/− mice were stimulated with LPS and IFN‐γ 43,44 . Cells were collected to detect the proportion of F4/80 + CD86 + cells after 24 h, which are indicative of M1 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…On day 7, the BMDMs were replated, and untreated (M0, CD11b + F4/80 + ) macrophages from WT and IL-28A −/− mice were stimulated with LPS and IFN-γ. 43,44 Cells were collected to detect the proportion of F4/80 + CD86 + cells after 24 h, which are indicative of M1 macrophages. IL-28A deficiency markedly reduced the proportion of M1 macrophages (Figure 7A).…”
Section: Il-28a Deficiency Inhibited M1 Macrophage Activation and The...mentioning
confidence: 99%
“…As widely documented in the literature, IL-4 stimulation is an effective method to polarize BMDMs to the M2 type. 37,38 Consequently, the macrophage phenotype in our co-culture system predominantly assumes the M2 type. After 20 h of incubation, we observed that the biomodulator BPC3 significantly enhanced the engulfment of the target cells by both M2-type macrophages and dendritic cells in vitro, indicating the favorable immunostimulatory ability of the PP1-disrupting motif (Fig.…”
Section: Biomaterials Science Papermentioning
confidence: 99%